PHYSICAL AND CHEMICAL NATURES OF POST ARTISANAL GOLD MINE AREA AT KEBUNLADO VILLAGE OF RIAU PROVINCE - Fauzul Amri; Reginawanti Hindersah; Benito R. Kurnani; Sunardi Sunardi; Martha Fani Cahyandito; Dedi Nursyamsi (Indonesian Mining Journal, 2020)
Illegal artisanal gold mining in Kebunlado, Riau Province has damaged the smallholders estate. The use of mercury for extracting the gold is potentially pollute the soil and syrrounding water as well as threats plantation productivity and it’s food chain. The purpose of this research is to study the mining impact towards the physical and chemical properties of the soil around the plantation, and measure the mercury contamination within the tailings, soil and river to be compared with the soil sample near the mine area. Sampling was carried out in 10 locations to study the properties of the land surrounding the artisanal gold mining. Physical and chemical properties of the soil were studied.The samples came from the mine sites (7 samples) and its surrounding area (3 samples). Sampling was conducted using a toposequence transect method, based on its topographical conditions and soil parent material with the purposive method. Mercury level was measured from eight soil samples that were sampled from surrounding artisanal mine area and six water samples from the surrounding rivers. The research showed that the soil characteristics had changed after mining activities. The soil properties were higher in sand, with bulk density and permeability compared to intact soil. However, there was no distinct change in pH, total nitrogen, organic carbon as well as available P, except C/N in post mine area was relatively low. Mercury content in the gold mine area was higher than that of the average mercury within the soil around the world. The Mercury in the river stream exceeds the threshold based on Indonesia Regulation. The study suggested that land reclamation is needed to develop oil palm plantation in terms of improving the soil physics, increasing C/N and remediation as well as reducing the mercury in soil and water.